The Empowerment of Livestock Farmers in Subclinical Mastitis Test with GAMA Anti-Haptoglobin in “Sahabat Ternak” Etawah Crossbreed Goat Farm - Fajar Budi Lestari; Madarina Wasissa; Siti Isrina Oktavia Salasia; Muhammad Novrizal Abdi Sahid (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
Sahabat Ternak is one of the Etawah crossbreed (PE) goat farm groups in Sleman. This farm group focuses on goat milk production and processed goods. Problems that commonly arise in dairy goat farms are the cases of subclinical mastitis, which are quite high. This disease may cause a decrease in milk production and quality. The mastitis subclinical detection method which is often used by the farming community is the somatic cell count (SCC) and California mastitis test (CMT). However, both tests have low accuracy. Recently, a new method named GAMA Anti-Haptoglobin, which is more accurate and can be done easily has been established by livestock farmers. This community service aims to empower livestock farmers in applying GAMA Anti-Haptoglobin as a sensitive, rapid, and accurate subclinical mastitis detection kit in Sahabat Ternak goat farm. The method used in this activity consisted of discussion, socialization, and training for livestock farmers, as well as laboratory testing, evaluation of test findings, and treatment for PE goats. After the training, the livestock farmers were able to apply GAMA Anti-Haptoglobin mastitis detection method effectively. The implementation of this easy and accurate field mastitis detection method, as well as personnel with reliable skills, will support in the decrease of mastitis cases and increase milk production and quality, as well as community welfare.